FAKTOR - FAKTOR YANG MEMPENGARUHI PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT - Anggia Restu Maulida, 12.05.52.0037; Himawan, Arief (Students Journal of Accounting and Banking, 2016)
The purpose of this study was to analyze the influence of time pressure, the risk of audit, review and quality control procedures, organizational commitment, professional commitment, audit experience, ethical awareness, and self-esteem supervision measures against premature termination on audit procedures. The population in this study is the auditor who works at KAP Central Java and Yogyakarta (DIY). The research sample was determined by Convenience Sampling (Sampling ease), which means the sample was taken spontaneously or by accident investigators met with respondents according to their characteristics. This study uses multiple regression analysis. The results of this study that partially (1) Time Pressure has a positive and significant impact on the premature termination of audit procedures; (2) Risk Audit has a positive and significant impact on the premature termination of audit procedures; (3) Review Procedure and Quality Control has a positive and significant impact on the premature termination of audit procedures; (4) Organizational Commitment has no effect on the premature termination of audit procedures; (5) Commitments Professionals have a significant negative effect on premature termination on the audit procedures; (6) Audit experience has no effect on the premature termination of audit procedures; (7) The Ethical Awareness has no effect on the premature termination of audit procedures; (8) Measures of Supervision has a negative and significant impact on the premature termination of audit procedures; and (9) Self Esteem has no effect on the premature termination of audit procedures. Â Keywords: Time Pressure, Risk Audit, Review Procedure And Quality Control, Organizational Commitment, Professional Commitment, Experience Audit, Ethical Awareness, Action Supervision, Self Esteem and Premature Termination Of The Audit Procedures